2006
DOI: 10.1074/jbc.m604959200
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Mice Expressing Dominant-negative Activin Receptor IB in Forebrain Neurons Reveal Novel Functions of Activin at Glutamatergic Synapses

Abstract: The transforming growth factor ␤ family member activin is an important regulator of development and tissue repair. It is strongly up-regulated after acute injury to the adult brain, and application of exogenous activin protects neurons in several lesion models. To explore the role of endogenous activin in the normal and acutely damaged brain, we generated transgenic mice expressing a dominant-negative activin receptor IB (dnActRIB) mutant in forebrain neurons. The functionality of the transgene was verified in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
79
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(83 citation statements)
references
References 26 publications
(31 reference statements)
2
79
1
1
Order By: Relevance
“…In hippocampal slices of dnActRIB mice, we found that the NMDA component of glutamatergic neurotransmission was decreased and, as a consequence, synaptic plasticity was impaired, causing a significant reduction in long-term potentiation (LTP) at the Schaffer-CA1 synapse. 7 These data were the first to demonstrate that endogenously produced activin is capable of modulating the performance of the major excitatory synapse in the brain. Here, we extended our study to the role of activin at the g-aminobutyric acid (GABA)ergic synapse.…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…In hippocampal slices of dnActRIB mice, we found that the NMDA component of glutamatergic neurotransmission was decreased and, as a consequence, synaptic plasticity was impaired, causing a significant reduction in long-term potentiation (LTP) at the Schaffer-CA1 synapse. 7 These data were the first to demonstrate that endogenously produced activin is capable of modulating the performance of the major excitatory synapse in the brain. Here, we extended our study to the role of activin at the g-aminobutyric acid (GABA)ergic synapse.…”
Section: Introductionmentioning
confidence: 91%
“…7 The founder mice were created by microinjection of fertilized oocytes from B6D2F2 Â C57BL/6 mice. Tg mice were backcrossed into the C57BL/6 strain for 6-10 generations before used for the experiments described in this study.…”
Section: Animalsmentioning
confidence: 99%
See 3 more Smart Citations